Chronic activation of the relaxin‐3 receptor on GABA neurons in rat ventral hippocampus promotes anxiety and social avoidance. Issue 10 (19th March 2019) - Rytova, Valeria; Ganella, Despina E.; Hawkes, David; Bathgate, Ross A. D.; Ma, Sherie; Gundlach, Andrew L.
Abstract: Anxiety disorders are highly prevalent in modern society and better treatments are required. Key brain areas and signaling systems underlying anxiety include prefrontal cortex, hippocampus, and amygdala, and monoaminergic and peptidergic systems, respectively. Hindbrain GABAergic projection neurons that express the peptide, relaxin‐3, broadly innervate the forebrain, particularly the septum and hippocampus, and relaxin‐3 acts via a Gi/o ‐protein‐coupled receptor known as the relaxin‐family peptide 3 receptor (RXFP3). Thus, relaxin‐3/RXFP3 signaling is implicated in modulation of arousal, motivation, mood, memory, and anxiety. Ventral hippocampus (vHip) is central to affective and cognitive processing and displays a high density of relaxin‐3‐positive nerve fibers and RXFP3 binding sites, but the identity of target neurons and associated effects on behavior are unknown. Therefore, in adult, male rats, we assessed the neurochemical nature of hippocampal RXFP3 mRNA‐expressing neurons and anxiety‐like and social behavior following chronic RXFP3 activation in vHip by viral vector expression of an RXFP3‐selective agonist peptide, R3/I5. RXFP3 mRNA detected by fluorescent in situ hybridization was topographically distributed across the hippocampus in somatostatin‐ and parvalbumin‐mRNA expressing GABA neurons. Chronic RXFP3 activation in vHip increased anxiety‐like behavior in the light–dark box and elevated‐plus maze, but not the large open‐field test, and reduced social interaction with a conspecific stranger. Our data reveal disruptive effects of persistent RXFP3 signaling on hippocampal GABA networks important in anxiety; and identify a potential therapeutic target for anxiety disorders that warrants further investigation in relevant preclinical models.